Thermal stability and decomposition study of epoxy/clay nanocomposites - Dzuhri, S.; Yuhana, N.Y.; Khairulazfar, M. (Universiti Kebangsaan Malaysia, 2015)
This study utilized the incorporation of nanoparticle filler into an epoxy system to study the effect of different nanosized montmorillonite (MMT) fillers on the thermal stability and mechanical properties of epoxy. The sample was prepared using diglycidyl ether of bisphenol A (DGEBA) with different surface treatments of montmorillonite filler by mechanical stirring. The results of thermal stability and mechanical properties of epoxy/clay system obtained from thermal gravimetric analyzer (TGA), universal testing machine (UTM) and scanning electron microscopy (SEM) were discussed. With the same amount of filler introduced into the system, different thermal stability of epoxy composite can be observed. Bentonite, which contained other contaminant components, can downgrade the enhanced properties of the filler.